IMPLEMENTATION OF ENTERPRISE ARCHITECTURE WITH TOGAF METHOD ON EMPLOYEE COOPERATIVE INFORMATION SYSTEM - Meithama, Dio Dikta (Jurnal Riset Sistem Informasi dan Teknologi Informasi (JURSISTEKNI), 2019)
Currently the world of technology and information systems has entered the era of 4.0 or even 5.0, then the thing that happens is that more and more organizations and agencies are trying to update their business process styles from manual to all-round technology. An organization, institution or agency really needs the support of an information technology to improve its performance and services to stakeholders. Likewise, what happened to the savings and loan cooperative PT. Indolakto Sukabumi to manage members 'data, loans, or members' deposits, this cooperative needs facilities and infrastructure that support the performance of its activities quickly, accurately and accurately. One of the things that must be done in this research, especially for the progress of this cooperative is to conduct analysis, research and implementation of an Enterprise Architecture can provide various benefits when combined with technology-based management systems and information will certainly be needed for all sectors of any organization. Implementation and implementation of EA Togaf Adm conducted in research in savings and loan cooperatives at PT. Indolakto Sukabumi is a very good breakthrough for the progress of the cooperative Keywords: Era 4.0, Era 5.0, cooperative, Enterprise Architecture, Togaf Adm.